Bulk magnetic properties of CdFe2O4 in nano-regime - Desai, R.; Mehta, R.V.; Upadhyay, R.V.; Gupta, A.; Praneet, A.; Rao, K.V. (My University, 2007)
Cadmium ferrite particles have been synthesized using co-precipitation technique followed by a low temperature (600°C) annealing in a time scale much shorter than reported in literature. Incorporation of sodium chloride during annealing helps to form a single phase spinel structure with a final particle size of around 50 nm. Even at such a short length scale we observe the overall magnetic properties to be similar to those of the bulk. The observed magnetic properties can be explained on the basis of an anti-ferromagnetic core with a shell containing 'ferromagnetic-like', but canted spin structure.
Keywords: Cadmium ferrite; Cation distribution; Disordered magnetic state; Fine particle